Menimbang Strategi Penatalaksanaan Deep Vein Thrombosis pada Pasien Strok Hemoragik - Raymond R. Tjandrawinata (MEDICINUS, 2025)
Hemorrhagic stroke is an acute condition with high morbidity and mortality rates, and is frequently accompanied by complications such as deep vein thrombosis (DVT). The main dilemma in managing DVT in this condition is a therapeutic paradox, where anticoagulants use is effective in preventing pulmonary embolism, but carries the risk of worsening intracranial bleeding. International guidelines recommend mechanical prophylaxis, such as intermittent pneumatic compression (IPC), and cautious use of low-dose anticoagulants in stable hematomas, although clinical evidence remains limited. Biological alternatives, such as DLBS1033, derived from Lumbricus rubellus, have shown potential safety and efficacy in case reports from Indonesia. Ethical perspectives, health policy, as well as pharmacological innovations andartificial intelligence, are essential to develop adaptive, equitable, and evidence-based strategies in the management of DVT following hemorrhagic stroke.